Analysis of light reflections on the coupling efficiency of a laser diode to a conically lensed single-mode fiber - Faidz, A. R.; Ghafouri-Shiraz, H.; Takahashi, K.; Chuah, H. T. (2000)
Conical microlenses fabricated at the end of single-mode fibers can increase the coupling efficiency between fibers and lasers diodes. In this letter, we present, for the first time, a theoretical analysis of the coupling efficiency between a laser diode and a conically lensed fiber, taking into account the effect of reflection from the lens surface. (C) 2000 John Wiley & Sons, Inc.